Laparoscopic total extraperitoneal inguinal hernia repair: A study at Rawalpindi Medical College and allied teaching hospitals - Hanif, Muhammad; Ahmed, Anis; Khan, Muhammad Mussadiq (Journal of Postgraduate Medical Institute, 2014)
Objective: To describe local experience of laparoscopic total extraperitoneal hernia repair in Rawalpindi Medical College (RMC) allied teaching hospitals. Methodology: A descriptive case series was conducted between 2007 and 2012 at Rawalpindi Medical College and Allied Teaching Hospitals including Benazir Bhutto Hospital, Holy Family Hospital and District Headquarter Hospital, Rawalpindi. Eighty seven patients of inguinal hernia were included through non-probability consecutive sampling. They underwent total extraperitoneal hernia repair. Sixty eight patients had unilateral hernia and 19 patients had bilateral hernias. Results: The mean age of the study population was 42.9±15.3 years (range: 13-75 years). The mean operation duration was 62±13 minutes (range: 35-90 min). For bilateral hernias the duration was longer; mean 103.66±23.4 minutes with a range of 75-180 minutes. Up to 4.6% had conversion to open surgery and 9.1% had complications. Overall, there were 3.4% hernia recurrences in one year follow up. The mean inpatient hospital stay was 1.85±0.65 days. Conclusion: TEP carries an acceptable complication rate, combining the advantages of minimal access surgery and mesh reinforcement of the groin. This approach is associated with short hospital stay and a low recurrence rate.